Burnout Assessment Tool (BAT): Validity evidence from Brazil and Portugal - Sinval, J.; Vazquez, A. C. S.; Hutz, C. S.; Schaufeli, W. B.; Silva, S. A. (International Journal of Environmental Research and Public Health, 2022)
The Burnout Assessment Tool (BAT) is gaining increased attention as a sound and innovative instrument in its conceptualization of burnout. BAT has been adapted by several countries, revealing promising validity evidence. This paper aims to present the psychometric properties of the Brazilian and Portuguese versions of the BAT in both the 23-item and 12-item versions. BAT’s validity evidence based on the internal structure (dimensionality, reliability, and measurement invariance) and validity evidence based on the relations to other variables are the focus of research. A cross-sectional study was conducted with two non-probabilistic convenience samples from two countries (N = 3103) one from Brazil (nBrazil = 2217) and one from Portugal (nPortugal = 886). BAT’s original structure was confirmed, and it achieved measurement invariance across countries. Using both classic test theory and item response theory as frameworks, the BAT presented good validity evidence based on the internal structure. Furthermore, the BAT showed good convergent evidence (i.e., work engagement, co-worker support, role clarity, work overload, and negative change). In conclusion, the psychometric properties of the BAT make this freely available instrument a promising way to measure and compare burnout levels of Portuguese and Brazilian workers.